Nucleation of Minerals: Precursors, Intermediates and Their Use in Materials Chemistry - Denis Gebauer (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Nucleation is the key event in mineralisation, but a general molecular understanding of phase separation mechanisms is still missing, despite more than 100 years of research in this field. In recent years, many studies have highlighted the occurrence of precursors and intermediates, which seem to challenge the assumptions underlying classical theories of nucleation and growth. This is especially true for the field of biomineralisation, where bio-inspired strategies take advantage of the special properties of the precursors and intermediates for the generation of advanced materials. All of this has led to the development of "non-classical" frameworks, which, however, often lack quantitative expressions for the evaluation and prediction of phase separation, growth and ripening processes, and are under considerable debate. It is thus evident that there is a crucial need for research into the early stages of mineral nucleation and growth, designed for the testing, refinement, and expansion of the different existing notions. This Special Issue of Minerals aims to bring together corresponding studies from all these areas, dealing with precursors and intermediates in mineralisation with the hope that it may contribute to the achievement of a better understanding of nucleation precursors and intermediates, and their target-oriented use in materials chemistry.